The Study of Meanings of Motifs on Artifacts Discovered from Archeological Sites of Gilan Province and their Classification based on Dumézil’s Trifunctional Model - Kazempoor, Ziba; Marasi, Mohsen (Journal of History Culture and Art Research, 2017)
Gilan is one of the historical centers which has drawn the attention of archeological and art researchers due to the fact that unique artistic works have been discovered from its archeological sites. The present study seeks to review the meanings of motifs on archeological artifacts discovered from Gilan and to classify the artifacts based on Dumézil’s trifunctional model. This study aims to increase awareness of form and content of designs on historical works of Gilan and to detail historical background of Gilan. To do this, motifs are classified and symbolic meanings of motifs of artifacts discovered from Gilan are consequently detailed. Finally, the three functions of the sacral, the martial and the economic which constitute Dumézil’s trifunctional model for social and cultural structure of Indo-European tribes are used to study the artifacts discovered from Gilan. In general, motifs on archeological artifacts of Gilan could be divided into four groups of plant, animal, human, and abstract which could be analyzed through Dumézil’s trifunctional model. Mixed animal motifs are related to first function and show a sacral function. The artifacts on which war and hunting scenes are represented are concerned with second Dumézil’s function namely “the martial”. Plant and animal motifs and some human figure designs such as figures of historical women are related to certain notions such as life and living which could be categorized into the economic function.